(untitled) (Lebenswelt. Aesthetics and philosophy of experience., 2014)
Desire is characterized by fluctuations in quality and quantity in most people, but sometimes these changes may result in a psychiatric condition. The spectrum of possible alterations is wide, and it may be characterized by very different clinical pictures. The main role of the neurobiological mechanisms that underlie desire is played by dopamine, a neurotransmitter whose concentration can be modified by use or abuse of several compounds, which may have a therapeutic role, in the case of medicines, or may lead to dysfunctional situations, in the case of substances or alcohol. Neuroimaging studies have allowed a better knowledge of brain areas involved in mental illnesses, recording functional changes during the execution of specific tasks. The improvement of these techniques in the near future will improve the choice of the most appropriate treatment for each disease, leading to patient tailored therapies. Different approaches to the treatment of disorders associated with an alteration of desire are currently available; often their combination, such as the one between psychophamacological drugs and psychotherapy, can lead to a better therapeutic result and to a reduction, or mitigation, of episodes’ of severity and recurrences.